2021
DOI: 10.1016/j.knee.2021.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Double-level osteotomy for severe varus osteoarthritic knees can prevent change in leg length and restore physiological joint geometry

Abstract: Background: It is unclear whether double-level osteotomy (DLO) combining closed-wedge osteotomy in the distal femur and open-wedge osteotomy in the proximal tibia deformity can prevent change in leg length and excessive coronal inclination of the tibial articular surface in surgical correction of the severe varus knee. The purpose of this study was to examine the postoperative change in leg length as well as radiological and clinical outcomes following DLO compared with the results obtained from knees undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…In contrast to the previous studies reporting unfavorable outcome of isolated HTO performed for this group of knees [ 30 , 39 , 42 ], the present study showed that DLO could yield significant clinical/radiological improvements even for advanced osteoarthritic knees. Consequently, the results of this study support the efficacy and validity of our surgical strategy of anatomical reconstruction of the bone and joint geometry via DLO [ 5 , 7 , 15 , 27 , 38 ]. In recent years, the surgical procedure for DLO has evolved to incorporate biplanar osteotomy and minimally invasive plate osteoosynthesis (MIPO) techniques [ 10 , 27 , 38 ], and the results have been reported in several studies [ 10 , 27 , 38 ].…”
Section: Discussionsupporting
confidence: 73%
“…In contrast to the previous studies reporting unfavorable outcome of isolated HTO performed for this group of knees [ 30 , 39 , 42 ], the present study showed that DLO could yield significant clinical/radiological improvements even for advanced osteoarthritic knees. Consequently, the results of this study support the efficacy and validity of our surgical strategy of anatomical reconstruction of the bone and joint geometry via DLO [ 5 , 7 , 15 , 27 , 38 ]. In recent years, the surgical procedure for DLO has evolved to incorporate biplanar osteotomy and minimally invasive plate osteoosynthesis (MIPO) techniques [ 10 , 27 , 38 ], and the results have been reported in several studies [ 10 , 27 , 38 ].…”
Section: Discussionsupporting
confidence: 73%
“…Based on the short follow-up period of the present study, the mid- and long-term quality of life remains unclear and needs further investigation. In addition to improvement in quality of life following DLO, previous studies reported good clinical midterm outcomes [ 5 , 22 , 28 ]. DLO can restore lower limb alignment and joint angles by preventing changes in leg length in varus malalignment.…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated in varus knee with reduced mechanical medial proximal tibia angle (mMPTA) [ 3 ]. Overcorrection producing a mMPTA out of the normal range (85–90°) is not recommended because this would lead to unphysiological joint-line orientation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%